Experimental Investigation on Long-Term Strength and Acoustic Emission Characteristics of Coal Pillar under Inclined Compression Loading - Chong Li; Sifeng He; Zhijun Xu (Geofluids)
Pillar rheological failure is one of the important reasons to induce earthquake, surface collapse, and water inrush disaster in underground mining engineering. Pillar is generally present under an inclined state and is significantly influenced by combining compression and shear loading. However, many scholars regard the long-term strength of coal or rock mass under pure uniaxial compression loading as the main evolution index of pillar strength, which is not consistent with engineering practice. In this paper, a new inclined uniaxial compression strength (IUCS) test system was developed and then used to carry out the IUCS test and creep test of coal specimens combined with an acoustic emission (AE) technology at various inclination angles (0°, 5°, 10°, 15°, and 20°). The variation of time-dependent deformation, peak strength, long-term strength (LTS), creep fracture model, and AE behavior of the coal with the inclination angels were discussed in detail. The results indicated that the peak strength and LTS of the coal nonlinearly decreased with the inclination angle increasing. The proportion of the peak strength to the LTS had remained constant between 58.5% and 62.9%, which can be considered as the inherent properties of coal rock. The creep failure model of the coal was transformed from tension-splitting failure at the inclination angle of 0° and 5° to tension-shear failure at the inclination angle of 10°-20°, which revealed that the inclination angles were favorable to the initiation and propagation of shear cracks. No matter any inclination angles, AE events can be divided into quiet period, low amplitude rising period, and high amplitude rising period with the periodic mutation of multistage loading points. Moreover, the cumulative AE energy gradually decreases with the increase of the inclination angles, which indicated that the shear stress caused by the specimen inclination can make crack initiation and propagation with less energy absorption. The research results will assist in the long-term strength design and time-dependent stability assessment of the coal pillar.